THE CONCENTRATION OF HEAVY METALS IN MARINE WATERS FROM PHU YEN TO BEN TRE - Vinh, Le Thi; Thom, Pham Van; Thu, Nguyen Hong; Kiem, Duong Trong; Tam, Pham Huu (Vietnam Journal of Marine Science and Technology, 2007)
Data obtained from investigations which have been carried out in the sea from Phu Yen to Ben Tre during 1999 - 2004 indicated that the heavy metal concentrations ranged from 1.3 to 23.1 μg/1 (mean 9.2 μg/1) for Zn; 0.3 - 5 .9 μg/1 (mean 2.7 μg/1) for Cu; 0.1 - 3.0 μg/1 (mean 1.3 μg/1) for Pb: 0.04- 0.4 μg/1 (mean 0.2 μg/1) for Cd: 0.45 - 5.7 μg/1 (mean 1.9 μg/1) for Cr: and 72.5 - 205.5 μg/1 (mean 121.9 μg/1) for Fe. Some data relating to As, Hg and Ni showed that As ranged from 1.2 to 5.9 μg/1 (mean 1.7 μg/1); Ni: 0.9 - 2.3 μg/1 (mean 1.44 μg/1): Hg: 0.07 - 0.62 μg/1 (mean 0.14 μg/1). Mean concentration of metals Zn, As, Cu were lower than those in Southeastern coastal sea and GulfofThailand, while mean concentration of Pb, Cu, Hg and Cd were similar. According to Vietnamese Standards for aquaculture waters, Zn in some stations exceeded the maximum allowable concentration and Fe exceeded the maximum allowable concentration in almost stations.